THE PLACE OF NON-ORIGINAL QUOTATIONS AS AN ARTISTIC METHOD (International journal of artificial intelligence, 2026)
This article discusses the role of reported speech that is not one's own as an artistic technique. Indeed, many linguists have pointed out that in literary texts, reported speech that is not one's own is considered one of the most effective methods of conveying someone else’s speech. In literary works, like other syntactic units, reported speech that is not one's own also has a place as an artistic technique. It appears that in achieving the author’s intended goal—evoking a certain response in the reader through the artistic portrayal of a character’s positive or negative traits—reported speech that is not one's own performs an important stylistic function.